(untitled) (Experimental biology, 2015)
Regeneration of adventitious shoots from wild species Tau-saghyz was achieved by induction of organogenesis in leaf explants. The highest values for organogenesis and regeneration in leaf explants of Scorzonera tau-saghyz Lipschits et Bosse were obtained due to positive influence of Gibberellic acid (GA3). The condition for creation suspension cell culture of tau-saghyz were studied.